Mass transfer : theory and applications - Narayanan, K.V.; Lakshmikutty, B. (New Delhi : Cbs publishers & Distributors pvt ltd., 2014)
It is intended to serve as a textbook for degree courses in chemical engineering and related disciplines such as petrochemical engineering, biotechnology, safety and fire engineering. It explains the theory, principles and applications of mass transfer techniques in detail in a student-friendly manner. It deals with the principles of molecular diffusion, theory of convective and interphase mass transport, the theory and application of the different separation techniques such as gas absorption, distillation, humidification and dehumidification, extraction, leaching, drying, crystallisation and absorption. The book provides a balanced mix of fundamentals and applications. State-of-the-art developments and trends in the design and construction of separation equipment and principles of their operation are covered in detail. An exhaustive coverage of the principles and applications of membranes and membrane separations is another highlight of this work. More than 157 worked out examples, about 660 exercise problems with answers, several hundred multiple choice questions and answers are included in this book.
introduction -- molecular diffusion -- convective transport and interphase mass transfer -- distillation -- humidification operations -- leaching -- drying -- adsorption -- crystallisation -- membrane separations -- answers to objective questions (MCQs) -- references
Includes bibliographical references and index.
Keywords: Heat -- Transmission; Mass transfer